The Impact of a Special Education Course on Pre-Service Teachers’ Knowledge and Perspectives about Inclusion and Inclusive Practices - Karal, Muhammed A.; Unluol-Unal, Neslihan; Tan, Sema (Journal of the American Academy of Special Education Professionals, 2023)
The purpose of this study was to examine the effect of a Special Education course on pre-school teacher candidates’ knowledge levels and perspectives towards inclusive practices as well as their willingness and self-confidence about working in an inclusive classroom. The single group pre-test- post-test design was conducted to see whether there was a change on the dependent variables. The study group consisted of 58 teacher candidates from a preschool teacher education program. The results of this study indicated that there was a statistically significant difference between the knowledge of the participants from the pre-test to post test. Based on the post-test results, teacher candidates’ willingness and self-confidence were significantly higher than the pre-test results. Limitations and implications for practice are presented.